Studi Konduktivitas Listrik Film Tipis Ba0.25Sr0.75TiO3 Yang Didadah Ferium Oksida (BFST) Menggunakan Metode Chemical Solution Deposition - Irzaman, Irzaman; Erviansyah, R; Syafutra, H; Maddu, A; Siswadi, Siswadi (BERKALA FISIKA, 2010)
Has done growth Ba0,25Sr0, 75TiO3 (BST) thin film and BST are pure Ferium Oxide Fe2O3 dopant (BFST) with dopant variations 5%, 10% and 15% above the substrate Si (100) type-p using Chemical Solution Deposition Method (CSD) with the spin coating technique at a speed of around 3000 rpm for 30 seconds. BST thin films made with 1 M concentration and annealing at a temperature of 850°C for Si Substrate. Thin film on silicon substrate type-p thickness characterization performed using the volumetric method and the characterization of electrical conductivity by using LCR meter. From the characterization results showed the thickness increases with the addition of ferium oxide dopant given. Electrical conductivity value of BST and BFST thin films are in the range semiconductor materials and electrical conductivity values obtained increased when the higher intensity light is used whereas resistance value could decrease if the light intensity is increased. The addition of ferium oxide dopant will increases electrical conductivity value of BST and BFST thin films. Keywords : BFST, thin film, CSD, spin coating, electrical conductivity